Concurrent multiscale topology optimisation towards design and additive manufacturing of bio-mimicking porous structures. Issue 1 (31st December 2023) - Lan, Tian; Do, Truong; Al-Ketan, Oraib; Fox, Kate; Tran, Phuong
ABSTRACT: This paper presents a novel multiscale explicit topology optimisation approach for concurrently optimizing the structure at the macro level and the bio-mimicking porous infillings at the micro level. Solid bar components with cross-section control at the macro level and sphere components at the micro level are constructed as the minimal control units to replace the manipulation of material distribution at each grid. The overlapping, moving and morphing of bar components provide the ability to generate flexible structural shapes at the macro level. Using the inspiration of the turtle shell (carapace), the sphere components are designed to move, overlap, and resize inside the bar to sufficiently mimic both the regular and irregular porous features. Classical beam designs, lattice structure designs and unit cell designs are illustrated as numerical examples to demonstrate the functionalities and correctness of the proposed method. As a result, the stochastic pores distribution and porosity control can be validated. The abilities of optimising lattice structure at truss-level and single unit cell level are demonstrated. Moreover, the samples are fabricated by selective laser melting (SLM) technology and then scanned with the X-ray micro-computed tomography (micro-CT) technique to further examine the manufacturability.